1990
DOI: 10.1002/ace.36719904810
|View full text |Cite
|
Sign up to set email alerts
|

Popular education: Models that contribute to the empowerment of learners in minority communities

Abstract: Some programs of adult education in the minority community that use the concept of popular education are reviewed. The dijkrent dimensions of popular education are explained, as well as how these dimensions aject the educational system by giving the participants a greater and more active role in it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The few studies that have been reported have employed a deficit perspective to interpret the Hispanic experience in adult education. The description of the educational experience of Hispanics is generally viewed as needing remedial language in order to assimilate culturally to U.S. society (Diaz-Lefebre, 1990;Facundo, 1984;Heany, 1989;Howlett, 1998;Jeria, 1990Jeria, , 1992Young and Padilla, 1990). Such outsider conceptual frameworks only perpetuate the damage done to learners in alien educational settings.…”
Section: Hispanics Absent From Adult Education Literaturementioning
confidence: 99%
“…The few studies that have been reported have employed a deficit perspective to interpret the Hispanic experience in adult education. The description of the educational experience of Hispanics is generally viewed as needing remedial language in order to assimilate culturally to U.S. society (Diaz-Lefebre, 1990;Facundo, 1984;Heany, 1989;Howlett, 1998;Jeria, 1990Jeria, , 1992Young and Padilla, 1990). Such outsider conceptual frameworks only perpetuate the damage done to learners in alien educational settings.…”
Section: Hispanics Absent From Adult Education Literaturementioning
confidence: 99%
“…On the other hand, some scholars have argued that community-based programs, in particular those guided by a popular education orientation, have provided viable alternatives for addressing the needs and interests of ethnic minority adult learners, such as foreign-and U.S.-born Latino men and women (Jeria, 1999). Yet, these efforts have often been weakened by the lack of precise knowledge of learners' perceptions on the part of educators and program leaders (Jeria, 1990). This inquiry has contributed to addressing this problem by providing a more specific understanding of the experiences and perceptions of adult learning that Central American immigrant women in the Midwestern United States have.…”
Section: Discussionmentioning
confidence: 99%
“…However, Jeria (1990) noted that the impact of popular education Studies of Central Americans have clearly indicated that gender, as a social system, has influenced the experiences of Central American immigrant women and men at various stages of the migration process (i.e., pre-migration, journey, settlement, and return). The literature suggests that immigration to the United States has presented women with challenges that are different from and often greater than those experienced by men.…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations